Poverty, Racism, & Sexism: The Reality of Oppression in America - Doob, Christopher Bates (Routledge, Taylor & Francis Group, 2021)
"Exploring the structural causes and consequences of inequalities based on a person's race, class, and gender, Poverty, Racism & Sexism: The Reality of Oppression in America concentrates on this formidable set of disadvantages, demonstrating how Americans are adversely affected by just one or a combination of three social factors. Grounded in sociological thought, the text highlights unfolding stories about major social inequalities and relentless campaigns for people's rights. Weaving together such concepts as individualism, social reproduction, social class, and intersectionality, the book provides a framework for readers to understand the vast injustices these groups encounter, where and why they originated, and why they continue to endure. Poverty, Racism & Sexism is a compact, versatile volume which will prove an invaluable resource for those studying social inequality, social problems, social stratification, contemporary American society, social change, urban sociology, and poverty and inequality"--
Keywords: Equality; Race relations; United States; Poverty; United States; Racism; United States; Sexism; United States; United States; dept.soc; faculty_collection